Tipologi Filsafat Pendidikan Islam: Kajian Konsep Manusia dan Tujuan Pendidikan Berbasis Filsafat Islam Klasik - M. ABDUL FATTAH SANTOSO; AZAKI KHOIRUDIN (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2018)
This study discusses typology of Islamic education philosophy derived from educational discourses in the classical Islamic philosophy. While existing construction of the philosophy of Islamic education is still heavily influenced by the Western philosophy, the current study investigates philosophical views of Islamic education from several philosophers in classical Islam. This research focuses on the question of human essence to discover the nature and purpose of Islamic education. The investigation of educational ideas is conducted on the branches of classical Islamic philosophy namely, Peripatetic philosophy (Ibn Sina), Herme- neutic-Pythagorean philosophy (Ikhwan al-Shafa), Illumination philosophy (Suhrawardi), Theosophy-Transcendent philosophy (Mulla Sadra). This study shows four typologies of Islamic studies philosophy, namely: Rationalism (Ibn Sina), Religious-Rationalism (Ikhwan al-Shafa), Enlightenment-Spiritualism (Suhrawardi), and Substantive-Spiritualism (Mulla Sadra)